Edukasi Ramadhan Sehat Melalui Media Poster untuk Meningkatkan Perilaku Hidup Sehat Masyarakat di Desa Ulee Lueng Aceh Besar - Noeroel Arham (JURNAL PENGABDIAN MASYARAKAT INDONESIA, 2026)
Ramadan is a period that requires changes in dietary patterns and daily activities, which can affect public health behavior. Lack of knowledge about healthy fasting practices often leads to unhealthy habits such as overeating, dehydration, and poor sleep patterns. This community service aimed to improve healthy living behavior during Ramadan through poster-based education in Ulee Lueng Village, Aceh Besar. The method used included health education, poster dissemination, and interactive discussions involving 35 community members. The activity was conducted in three stages: preparation, implementation, and evaluation. Data were collected through pre-test and post-test questionnaires to measure changes in knowledge and behavior. The results showed a significant improvement in participants’ understanding of healthy fasting practices, including balanced nutrition, adequate hydration, and maintaining physical activity. Posters proved to be an effective educational medium due to their visual appeal and ease of understanding. This program contributed to increased awareness and positive behavioral changes in the community. It is recommended that similar programs be implemented continuously with varied media to strengthen public health promotion.